Adequacy of Lymph Node Staging in Colorectal Cancer: Analysis of 250 Patients and Analytical Literature Review - Leila Ghahramani; Samira Razzaghi; Mohammad Mohammadianpanah; Saeedeh Pourahmad (Iranian Journal of Colorectal Research, 2013)
Background The extent of lymph node involvement is the most important prognostic factor in resected locoregional colorectal cancer. Currently, examination of at least 12 lymph nodes is recommended for adequate colorectal cancer staging. Objectives The present study aimed to evaluate the adequacy of lymph node staging in 250 patients with colorectal cancer and analytical literature review. Patients and Methods Two hundred fifty patients with histologically proven locoregional invasive colorectal adenocarcinoma from 2005 to 2011 were included. All patients were treated by standard surgical resection for their disease. Twenty-three patients with rectal cancer received neoadjuvant treatment. All potential tumor, patient and treatment variables were evaluated for their impact on the average total number of lymph node examined. Results In this study, 147 men and 103 women with a median age of 54 (range 23-84) years were included. The median total number of lymph nodes examined was 7 (mean 9.35). Sixty-nine patients (27.6%) had adequate (≥ 12) lymph nodes examination, and twenty patients (8%) had no nodes examined. In univariate analysis, younger age, colon primary site, larger tumor size, the presence of lymphatic vascular invasion, the lack of neoadjuvant treatments, individual surgeon B and Hospital B were more associated with the average total number of lymph node examined. Conclusion This study indicates that only less than a third of patients with colorectal cancer underwent adequate lymph nodes examination. Further investigation using careful pathologic reviewing of specimens with inadequate lymph node examined is suggested for differentiating true inadequate lymph node dissection from inadequate lymph node detection.